Mineral analysis in rocks using XRD and Petrography - Muhamad Ragil Setiawan; Mochamad Iqbal; Rahmat Nawi Siregar (Journal of Science and Applicative Technology, 2019)
Rock formation in a region is influenced by many factors such as tectonic and volcanic systems of the area. Both activities will affect the microstructure of the rock. This study analyzes mineral composition in three different rocks. We display the digital image that obtained from XRD and petrography. Rock samples were taken from some formations around Lampung. The analysis was performed on three different rocks: granite, andesite, and schist using XRD and petrography. The granite-R1 sample shows the result of mineral content present in the rock that is quartz, alkali feldspar, plagioclase, biotite. The andesite-R2 sample consists of plagioclase, orthopyroxene, biotite, and volcanic glass. The Schist-R3 sample consist of quartz, muscovite, calcite.